Synthesis, structure and reactivity of azosalophen complexes of palladium - Pattanayak, Poulami; Pratihar, Jahar Lal; Patra, Debprasad; Puranik, Vedavati G.; Chattopadhyay, Surajit (Polyhedron, 2008)
The ligands 2-(arylazo)-1-N-salicylidene phenylamine, H(2)L(sal), (where H represents the dissociable protons upon complexation) afford stable orthopalladated complexes, [(L(sal))Pd], upon treatment with Na(2)[PdCl(4)]. The dinegative anionic (L(sal))(2-) ligands bind Pd(II) in a tetradentate (C, N, N, O) fashion with a distorted square planar geometry. The newly synthesized palladium complexes underwent oxygen insertion into the Pd-C bond with mCPBA (m-chloroperbenzoic acid) or TBHP (terbutylhydroperoxide)/[VO(acac)(2)] leading to the formation of stable azosalophen complexes of Pd(II) with the (O, N, N, O) coordination mode of the oxygenated ligand. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: 2-(arylazo)-1-N-salicylidene phenylamine; azosalophen complex; orthopalladation; oxygen insertion